Modeling economic growth in contemporary Malaysia - Sergi, Bruno S.; Jaaffar, Abdul Rahman (Entrepreneurship and global economic growth., 2021)
In the current global market, which is turbulent, volatile, and continuously changing, companies must consistently sustain and survive during turbulent times. Although Malaysia is paving a way to adapt to the advancement of technology, one of its biggest challenges is sourcing the knowledge, skills, and competencies that will supply solutions to transform Malaysia into high value competitor for industrial countries. The newest book in the Entrepreneurship and Global Economic Growth series, Modelling Economic Growth in Contemporary Malaysia considers the crucial changes to Malaysian economic areas and social well-being. Exploring issues from various perspectives including entrepreneurship, economic, financial, banking, marketing, and human resource, the chapters cover diverse industries such as IT, green technology, retailing, banking, tourism and hospitality, education, logistics, finance, banking, and many others. Acknowledging that Malaysian companies must embrace the notion that human capital is a crucial contributor to competitive advantage, this book brings forward consumers' behavioral issues from the marketing lens, offering a critical exploration of how money spending interacts with choices relating to desired products or services.